(untitled) (Szociológiai Szemle, 2024)
The paper offers a critical review of the so called „market transition debate”, using Nee’s 1989 ASR article as its point of departure. It identifies three major dimensions of the controversy: a) can market play an equalizing role in an economic system? b) who benefits from the expansion of markets, cadres or ordinary people? c) is the theory of market transition teleological? The main hypothesis of the paper is that at least as far as the first two question is concerned the answer really should be „it depends”. Both those who accept market transition theory and those who reject it make the error or overgeneralizing from their evidence. This paper instead suggests that the task of social research is to identify under what circumstances, what type and degree of market penetration produces equalizing effects, what sort of markets benefit cadres or former cadres, and what sort of markets were used by ordinary people to improve their life chances. The paper offers a number of empirically testable hypotheses along these lines.